2005
DOI: 10.1016/j.ejogrb.2004.11.021
|View full text |Cite
|
Sign up to set email alerts
|

A historical perspective on pregnancy-related low back and/or pelvic girdle pain

Abstract: The growing interest in pregnancy-related low back and/or pelvic girdle pain has invoked research projects to this subject. Although it seems a modern syndrome, historical articles show that pregnancy-related pelvic girdle pain (PPGP) was already known centuries ago. The purpose of the present article is to provide a summary review of performed studies on pregnancy-related pelvic girdle pain. Remarkably, these studies show large differences in results with regard to, for example, incidence rates and relevant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 53 publications
2
76
1
4
Order By: Relevance
“…The ODI was treated as a continuous scale. The initial choice of possible predictors was based on the hypothesis of an association between muscle dysfunction and PGP, as well as on previous findings in the literature [1,2,7,10,11,[20][21][22].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The ODI was treated as a continuous scale. The initial choice of possible predictors was based on the hypothesis of an association between muscle dysfunction and PGP, as well as on previous findings in the literature [1,2,7,10,11,[20][21][22].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Many studies fail to discriminate different patterns of clinical presentation of low back ache namely -PPGP, LBP, and combined. 4 Very few studies in literature distinguish between PPGP and PLBP. Ostgaard et al from Sweden in prospective cohort study between 12 weeks of pregnancy and 1 year after delivery at 4 weeks interval screened 855 pregnant women for lumbar pain using self-reported questionnaire pain mapping and visual analogue scale found a point prevalence of 25% PLPP.…”
Section: Resultsmentioning
confidence: 99%
“…In 1928 more than 20 mm of joint space was considered as marked diastasis by Bren and Weiranch, in 1932 Hayman Lundquis observed that widening of symphysis pubis starts in early pregnancy, and continues up to 3 to 4 months before parturition. 4 Later, Ostgaard et al, set the criteria for the differentiation between these two entities. It has been estimated that about 50% of pregnant women will suffer from some kind of low back pain at some point during their pregnancies or during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][21][22][23][24] El desarrollo de una identificación de los factores de riesgo de la salud y calidad de vida de embarazadas permite reducir una sobrecarga de la mujer, poniendo en riesgo su desarrollo tanto laboral como en su embarazo. [25][26][27][28] Por lo anterior, es necesario contextualizar desde el punto de vista del factor físico-biomecánico a que se encuentran sometidas las trabajadoras embarazadas, a través de la descripción de los mismos, determinar las dimensiones de la carga global de trabajo, presencia de factores físico-ergonómicos y la percepción de molestias músculo-esqueléticas de trabajadoras en situación de embarazo, que puedan servir de base para determinar recomendaciones iniciales que ayuden en el autocuidado de las embarazadas.…”
Section: Introductionunclassified